Multilingual and multimodal mediation in online intercultural conversations: a translingual perspective. Issue 3 (5th October 2021) - Liang, Mei-Ya
Abstract: This study explored peer groups' mediation processes in the digital space. Building upon translingual research and multimodal discourse analysis, the researcher analysed video transcript excerpts of oral conversations and on-screen interactions among university students of different linguistic and cultural backgrounds. This article focuses on multilingual and multimodal mediation practices, which include polyaccented exemplification, bilingual interpretation, intercultural comparison, transnational definition, polyphonic performance and multimodal instruction ( N  = 24). The results show that the students attended to dynamic uses of English, Chinese and other languages as multilingual franca while communicating affect and stance through embodied expressions and shared screens in stylised multimodal discourses. The translingual analyses emphasise the students' collaborative transformations of English as a lingua franca (ELF) communication into playful interactions within digitally mediated networks of relationships. This study suggests that online peer mediation provides useful methods for developing university students' translingual awareness and capability for participating in intercultural conversations.